Contract‐Based Knowledge Protection and Cooperation Performance: The Effects of Technological Turbulence and Legal System Completeness. (26th October 2021) - Wang, Li; Wang, Longwei; Zhang, Min
Abstract: This study examines the direct effects of technological turbulence and legal system completeness on contract‐based knowledge protection and the moderating effects of these factors on the relationship between contract‐based knowledge protection and cooperation performance. A conceptual model is developed using the sensemaking perspective. The model is tested using survey data collected from 227 manufacturing firms in China. We find that contract‐based knowledge protection is positively associated with cooperation performance. Technological turbulence and legal system completeness both have significant positive effects on contract‐based knowledge protection. In addition, technological turbulence weakens the positive relationship between contract‐based knowledge protection and cooperation performance, while legal system completeness strengthens the relationship. The findings enrich existing knowledge on how technological and legal environments shape firms' decisions on knowledge protection in cooperation and moderate its effect on performance outcomes.